Ultrasound-guided microwave ablation in the treatment of early-stage tongue cancer - Yang, Jianquan; Guo, Wen; Huang, Rong; Xu, Zhengmin; Zhou, Chunyang; Lu, Man (Frontiers in Oncology, 2022)
Background Tongue cancer is a common malignant tumor of the head and neck. Its treatment methods include surgery, radiotherapy, and chemotherapy. However, these treatments have serious side effects and poor cosmetic effect, so it is urgent to find new treatment methods. We pioneered the use of microwave ablation (MWA) in the treatment of early tongue cancer and achieved good results. Case Presentation A 67-year-old woman (Han nationality) was admitted to the hospital because of progressive aggravation of tongue pain. She had a history of tongue pain of more than 1 year. Pathological biopsy showed squamous cell carcinoma; following this, radical operation of the tongue cancer was planned. The preoperative examination showed thyroid occupation in the upper mediastinum region compressing the airway; hence, the risk of general anesthesia was high. Consent was obtained from the patient and her family. Ultrasound-guided MWA was successfully performed under the lingual nerve block. The patient was followed for 1 year. She recovered well with no dysphagia and unclear articulation symptoms, and the cosmetic effect was excellent. Conclusion To our knowledge, this is the first case of using MWA for the treatment of early-stage tongue cancer (ESTC). Ultrasound-guided MWA may be used for ESTC that can completely ablate the tumor and retain the function of the tongue, further improving the quality of life of the patient. However, it is only a case report and needs more research to verify the use of MWA in ESTC.